How reputation bridging nowness service and memorable tourism experience to achieve tourism sustainable development goals - Ratih Pratiwi; Windi Novia Ratri Wardhani; Devi Trihandari Widyatania; Dasmadi Dasmadi (Universitas Merdeka Malang, 2023)
Social media will be an integral part of any digital marketing strategy for the tourism industry, but it's important to remember that this medium produces content with wide variations. Tourist hotspots need to keep a positive online reputation so that positive word-of-mouth spreads among locals. This research aims to fill this knowledge gap by proposing an integrated model to investigate the impact of destination reputation and nowness service on visitors likelihood to return and by extension, on sustainability. Assessment of the measurement model in this study used SEM PLS, and data were collected from 70 people in Central Java province. A positive correlation between Nowness service and destination reputation was found, suggesting that the more popular a destination is, the more positive its reputation will be perceived to be. Having a positive impact on the visitor’s perception of the destination, a memorable vacation is a great marketing tool. The ability to provide visitors with a memorable experience and excellent service while also considering the concept of sustainability in terms of the economy, environment, and society is essential to a destination's reputation, which in turn generates a sustainable competitive advantage in the tourism industry. The following section discusses the implications and the agenda for future research.